Metode Komunikasi Dakwah Jama’ah Tabligh di Masjid Lawang Kidul Kota Palembang - Ahmad Dairobi; Purmansyah Ariadi (Fakultas Agama Islam Universitas Muhammadiyah Palembang, 2026)
The purpose of this study is to determine the da'wah communication methods of Jama'ah Tabligh, its effectiveness, and the problems it faces at the Lawang Kidul Mosque, Palembang. This study uses a qualitative method with a case study approach. The data collection tools are observation, in-depth interviews, and documentation. The types and sources of data used are primary and secondary. The analysis techniques used are data reduction, data presentation, and conclusion drawing. From the results of the study, (1) The da'wah communication method of Jama'ah Tabligh is holistic, combining a verbal approach (tamsil), empathetic non-verbal communication (dakwah bil-hal), and an a-technological philosophy (mujahada). (2) This method is proven to be highly effective in producing deep personal transformations in individuals and successfully building a positive image in the community. (3) The main problems faced are not ideological rejection, but practical friction with the mosque administrators regarding issues of cleanliness, tidiness, and a lack of logistical coordination.